Evaluating Teff Grass as a Summer Forage - J. M. Davidson; D. Min; R. M. Aiken; G. J. Kluitenberg (Kansas Agricultural Experiment Station Research Reports, 2018)
The objectives of this study were to determine the forage yield, nutritive value, and water use efficiency of teff grass (Eragrostis tef) under field conditions as compared to sorghum sudangrass and forage pearl millet. Water use efficiency was determined by regressing above-ground biomass on crop water use between sampling periods. Yield was determined by quadrat area clippings of above-ground biomass. Nutritive value was determined using wet chemical analysis. Cultivars showed significant differences in biomass production at all sampling dates in both years. Teff grass demonstrated potential to provide producers with a fast-growing and competitive forage crop by reaching optimum yields at an earlier date than other commonly grown forages.
Keywords: forage; teff grass; water use efficiency; nutritive value